The Role of Islamic Religious Education Teachers in Implementing Religious Culture among Grade VIII Students at SMP Negeri 1 Kulisusu, North Buton Regency - Sumarno Sumarno; Abdul Rahim; Jufri Jufri (Civiliza Publishing, Indonesia., 2026)
This study examines the role of Islamic Religious Education (PAI) teachers in implementing religious culture among Grade VIII students at SMP Negeri 1 Kulisusu, North Buton Regency. Using a qualitative case study design, data were collected through in-depth interviews with key school stakeholders, observations of religious routines and student interactions, and analysis of relevant school documents. The findings show that religious culture is implemented through integrated habituation practices embedded in daily and periodic school activities, including greeting (salam), prayers before and after lessons, Qur’an recitation (tadarus) at particular moments, strengthening worship discipline, and infaq/charity practices aimed at fostering social care. These practices are sustained through four main mechanisms: habituation, teacher modeling, reinforcement, and monitoring. The study further reveals that PAI teachers play a strategic and multi-dimensional role as program planners, implementers and mentors, role models (uswah), motivators and moral counselors, and evaluators who monitor behavioral change and program continuity in coordination with homeroom teachers and the student affairs unit. Positive impacts are reflected in improved discipline, politeness, and increased participation of many students in religious activities. However, the effects are not evenly distributed due to differences in family support, peer influence, and students’ personal motivation, as well as structural constraints such as limited time and varying classroom commitment. This study implies that strengthening school religious culture requires consistent routines, strong teacher modeling, educational reinforcement, and systematic coordination across school units, alongside enhanced school–parent collaboration. These elements are crucial to ensure the sustainable internalization of religious values and the development of students’ religious character in early adolescence.